Correlation between plasma hydrogen sulfide and homocysteine in patients with acute promyelocytic leukemia - Ling Fan (Journal of Hainan Medical University, 2017)
Objective: To investigate the correlation between plasma hydrogen sulfide (H2S), homocysteine (Hcy), folic acid and vitamin B12 in patients with acute promyelocytic leukemia (APL) before and after treatment. Methods: A total of 26 hospitalized patients with APL were randomly selected as case group and 26 healthy persons as control group. The concentration of H2S, Hcy and folic acid in plasma of case group and control group were measured, respectively. The statistically significant difference was investigated by comparing the acute onset phase and clinical remission of case group with those of healthy control group. Results: The concentration of H2S and Hcy of plasma in patients of case group during acute onset phase significantly increased, and concentration of folic acid significantly decreased, and there were both statistically significant differences as compared with those during clinical remission and those of control group (P<0.01). The concentration of H2S and Hcy of plasma in patients of case group during clinical remission after treatment decreased, and concentration of folic acid increased. The result was close to that of healthy control group, and there was no statistically significant difference (P>0.05). The change in concentration of plasma H2S was positively correlated with that of Hcy and negatively correlated with that of folic acid in patients of case group before and after treatment. Conclusions: The increase of plasma H2S in patients with APL may be related to the changes in concentration of Hcy and folic acid.